Political Framing and Elite Delegitimation in YouTube Narratives of the Sumatra Flood Crisis - Muhamad Hanif Fuadi; Frista Fitriany Ramadhanita; AH. Khairul Wafa (PT Agung Media Publisher, 2026)
This study examines how political disaster narratives are constructed and contested in YouTube content criticizing elite responses during the Sumatra flood crisis at the end of 2025. Employing a qualitative approach, the research integrates Critical Discourse Analysis with Entman’s framing model to analyze verbal, visual, and intertextual elements in selected YouTube videos that explicitly address government preparedness, elite political imagery, defensive responses, and structural–technical explanations of disaster causality. The analysis is based on a purposively selected dataset of high-engagement YouTube videos published in the immediate aftermath of the disaster, drawn from news programs and political commentary channels that consistently engage with elite criticism. The analytical scope focuses on narrative structure, visual juxtaposition, rhetorical strategies, and moral evaluations embedded in disaster-related political communication. The findings reveal four dominant framing patterns: government unpreparedness, the symbolic imagery of political elites, responsive versus unresponsive elite positioning, and technical–structural framing of disaster causes. Beyond identifying these patterns, the study demonstrates how YouTube reallocates framing authority from state-centered actors and mainstream journalism to non-state digital actors, enabling disaster narratives to function as mechanisms of political delegitimization in digital public spaces. Theoretically, this study contributes to disaster framing and political communication literature by positioning YouTube as an autonomous political actor that reshapes crisis communication dynamics, blurs the boundary between journalism and activism, and redistributes symbolic power during humanitarian emergencies. The findings underscore that contemporary disasters are not only humanitarian crises but also digitally mediated political battlegrounds that actively shape public trust, elite legitimacy, and democratic accountability.